COPYRIGHT BINDING AND ASSESSMENT AS A FIDUCIARY GUARANTEE IN CREDIT AGREEMENTS IN INDONESIA - Ade Riyan Permana; Prihati Yuniarlin (LPPM STIH Putri Maharaja, 2025)
Copyright in Indonesia, as protected by Law No. 28 of 2014, comprises moral rights and economic rights. Copyright, under Article 16 of the Copyright Law, is an intangible movable object that can be used as a fiduciary guarantee, thereby enabling potential credit through banking or non-banking institutions using copyright as collateral. Therefore, this research aims to understand the binding and valuation of copyright as an object of fiduciary collateral in credit agreements in Indonesia. This legal research method uses normative legal research, namely through library study, with a legislative and conceptual approach. The research results show that Copyright can be used as an object of fiduciary collateral in credit agreements, namely through the encumbrance of Copyright based on a notarial deed, including the Copyright certificate, which in this case serves as the primary collateral, and then the licensing agreement, which in this case serves as a source of profit (as additional collateral). The economic valuation of Copyright collateral uses several approaches, including the cost approach, market approach, income approach, and other approaches as defined by valuation standards. However, until now, there are no Bank Indonesia regulations governing Copyright as collateral, nor are there guidelines for determining the liquidation value of Copyright as fiduciary collateral in Indonesia.